REVISION OF LATE MESSINIAN LYMNOCARDIINAE (BIVALVIA)FROM PIEDMONT (NW ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2012)
The paper discusses a revised interpretation of the Late Messinian malacofaunas of Piedmont, namely the bivalves of the subfamily Lymnocardiinae (family Cardiidae), which are kept at the Museo Regionale di Scienze Naturali of Turin and the Museo Civico Archeologico e di Scienze Naturali "Federico Eusebio" of Alba (Cuneo). The historical Bellardi and Sacco collection in Turin contains various specimens of Lymnocardiinae that F. Sacco collected from various sites in the provinces of Cuneo and Alessandria (Piedmont) at the end of the 19th century. The Alba museum holds several species that O. Cavallo and G. Repetto found in the Alba area in the 1980-1990s. The authors of the paper deemed it necessary to reinvestigate the above-mentioned material, in spite of its non-optimal conservation status, because it testifies the high specific diversity of the Late Messinian “lago-mare” molluscan assemblages of Piedmont, whose original deposits are often no longer accessible. Both Pontian Paratethyan taxa and Late Messinian Mediterranean endemics were recognised. Fifteen species referable to five genera were identified. Five species have been left in open nomenclature, due to poor preservation and scarcity of material, and a new species of Lymnocardiinae, referable to the genus Pseudocatillus Andrussov, was described: Pseudocatillus nevesskayae n. sp.